(untitled) (Latakia University Journal -Medical Sciences Series, 2024)
Background: Laparoscopic cholecystectomy is considered the most commonly performed operation and as the standard treatment for cholelithiasis. Difficult cholecystectomy is associated with serious complications and high rate of surgical conversion. Aim: The purpose of this study was to investigate the predictive factors for difficult laparoscopic cholecystectomy. Materials and Methods: This was an analytical study (cross sectional) involving 156 patients who underwent laparoscopic cholecystectomy. They were selected from Department of General surgery, Tishreen University Hospital, Lattakia, during the period 2022-2023. Results: Out of 156 patients, 46 were male and 110 were female. Mean age of the patients was 62.13±7.4 years with presence of diabetes mellitus(DM) in 14 cases(9%). According to Randhawa score, cholecystectomy was easy in 138 cases(88.5%) and difficult in 18 cases(11.5%) with detecting operative difficulty in laparoscopic cholecystectomy in 111 cases(71.2%). Cholecystectomy was more difficult in patients older than 50 years(p:0.04) and with increasing body mass index(BMI)(p:0.03). There were no significant differences regarding of difficult cholecystectomy according to gender(p:0.9), precence of DM(p:0.2), previous history of ERCP(p:0.3), hospitalization for cholecystitis (p:0.07), prior abdominal surgery(p:0.2), levels of CRP(p:0.8), echographic findings including thickening of the gallbladder wall(p:0.08), pericholecystic fluid(p:0.1), impacted stone in gallbladder neck(p:0.1), and Randhawa score(p:0.07). Accuracy, sensitivity, specificity, and positive predictive value of Randhawa score were37.82%, 14.41%,95.55%, and 88.88% respectively. In addition to, cholecystectomy was easy in 61 cases(39.1%) and difficult in 95 cases(60.9%) according to modified Randhawa score depending on the most statistically significant factors with accuracy, sensitivity, specificity, and positive predictive value: 69.23%,71.17%, 64.44%, and 83.15% respectively. Conclusion: The current study demonstrated the importance of use preoperative scale to predict the difficulty of surgery in patients who are planning laparoscopic cholecystectomy , inform patient with adequate preoperative planning and request support if necessary.